2014
DOI: 10.1007/s12560-014-9148-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Genetic Analysis of Salivirus/Klassevirus in Wastewater in Arizona, USA

Abstract: Salivirus/klassevirus sequences were identified in 7 (15 %) wastewater samples collected in Arizona monthly for a year, with the highest concentration of 2.28 9 10 5 and 2.46 9 10 4 copies/L in influent and effluent, respectively. This is the first report of quantification and genetic analysis of salivirus/klassevirus in water samples in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The number of copies of RNA detected increased by ten times over a period of 20 days, during which the number of COVID-19 patients also increased by two times in Ahmedabad. A similar correlation between the number of SARS-CoV-2 RNA and the number of COVID-19 patients was also observed in Australia, China, and France [76] , [77] , [78] , [79] . Kitajima et al (2020) reported 2 × 10 5 and 3 × 10 4 copies/L SARS-CoV-2 RNA copies/L in the wastewater of Massachusetts, United States of America, and Bozeman, Montana, respectively, while wastewater in France accounted for 10 5 to 10 6 SARS-CoV-2 RNA copies/L [80] .…”
Section: Characteristics Of Hospital Wastewatersupporting
confidence: 75%
“…The number of copies of RNA detected increased by ten times over a period of 20 days, during which the number of COVID-19 patients also increased by two times in Ahmedabad. A similar correlation between the number of SARS-CoV-2 RNA and the number of COVID-19 patients was also observed in Australia, China, and France [76] , [77] , [78] , [79] . Kitajima et al (2020) reported 2 × 10 5 and 3 × 10 4 copies/L SARS-CoV-2 RNA copies/L in the wastewater of Massachusetts, United States of America, and Bozeman, Montana, respectively, while wastewater in France accounted for 10 5 to 10 6 SARS-CoV-2 RNA copies/L [80] .…”
Section: Characteristics Of Hospital Wastewatersupporting
confidence: 75%
“…In South Korea, 57.1% (8/14) of the incoming sewage samples collected monthly from a wastewater treatment plant were positive for salivirus in years 2010/2012 in Seoul . Salivirus sequences were also identified in 7 (15%) wastewater samples collected in Arizona, United States, monthly for a year in 2011/2012, with the highest concentration of 2.28 × 10 5 and 2.46 × 10 4 copies per liter in influent and effluent, respectively . In this study, 3 to 12 different salivirus sequences were identified per sample, indicating the genetic variations of salivirus.…”
Section: Salivirus In Environmental Samplesmentioning
confidence: 52%
“…More recently, Haramoto and Otagiri reported the detection of HCoSV in wastewater and river water in Japan, demonstrating a high prevalence in tested samples (raw sewage, 71 %; secondary-treated sewage, 29 %; river water, 29 %) with the highest concentration of 2.80 9 10 6 copies/liter in raw sewage [7]. Moreover, our recent work revealed the presence of another emerging picornavirus potentially associated with infantile gastroenteritis and AFP, namely, salivirus/klassevirus, in wastewater samples collected from Arizona, the United States [8]. These recent findings prompted us to carry out a year-long investigation on the occurrence and genetic diversity of HCoSV in wastewater in Arizona.…”
Section: Introductionmentioning
confidence: 76%